Pelaksanaan Ekstrakurikuler Bola Voli pada Sekolah Dasar - Muhammad Supriyadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
This study aims to describe the implementation of bolavoli extracurricular in SDN 85 Lubuklinggau. The population of this study were all students who participated in the implementation of volleyball extracurricular totaling 30 people. The sample in this study was taken using a total sampling technique where the sample in this study was the entirety of the research population of 30 people. Data collection techniques using a research instrument questionnaire with a Likert scale. The results of data analysis, 1) the level of achievement of students 'motivation in the implementation of volleyball extracurricular activities is in the classification of Enough, namely the level of achievement of respondents' answers reached 60%, 2) the level of achievement of facilities and infrastructure in the implementation of volleyball extracurricular activities is in the classification of Good, ie with a level of achievement of 62%. Conclusion, volleyball extracurricular implementation is in good category. Keywords: Implementation, Extracurricular, Volleyball